Insights into the Binding of Cyclic RGD Peptidomimetics to α5β1 Integrin by using Live‐Cell NMR And Computational Studies. Issue 1 (9th December 2016) - Guzzetti, Ileana; Civera, Monica; Vasile, Francesca; Arosio, Daniela; Tringali, Cristina; Piarulli, Umberto; Gennari, Cesare; Pignataro, Luca; Belvisi, Laura; Potenza, Donatella
Abstract: The interaction of a small library of cyclic DKP–RGD peptidomimetics with α5 β1 integrin has been investigated by means of an integrated experimental and computational approach. Bioaffinity NMR techniques, including saturation transfer difference (STD) and transferred NOESY, were applied to the ligands in a suspension of intact MDA‐MB‐231 breast cancer cells, in which integrin α5 β1 is highly expressed. The NMR data were compared with the docking calculations of the RGD ligands in the crystal structure of the α5 β1 binding site, and were integrated with competitive binding assays to the purified α5 β1 integrin. Ligand binding epitopes involve protons of both the RGD moiety and the DKP scaffold, although the stereochemistry and the functionalization of the DKP scaffold as well as the macrocycle conformation determine a great variability in the interaction. The ligand showing the highest number of STD signals is also the most potent α5 β1 ligand of the series, displaying a nanomolar IC 50 value. Abstract : Cells do it better ! The interactions between breast cancer cells, expressing high levels of integrin α5 β1, and cyclic DKP–RGD peptidomimetics are studied by using bioaffinity NMR techniques. The NMR data are compared with the docking calculations of RGD ligands in the crystal structure of the α5 β1 binding site, thus affording an improved understanding of ligand–integrin interactions.